(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
Currently, one-hundred seventeen survived registers witness the scriptorìa activity which took place in Archivium romanae curiae, founded at the end of 1507 by pope Iulius II. Among them, Liber 1 instrumentorum – called Secretus – was used to collect acts that had to remain confidential. In this paper Secretus, also described from a material point of view, is investigated in its features and functions in the light of pontifical legislation. Finally, the article provides regesta of acts dated from 1506 to 1524, increasing in this way the knowledge about this office section functioning and, more generally, negotiation activity of ecclesiastical and lay people who gravitated around the papal court in the late Renaissance.